PRINCIPLES AND HUMAN FACTOR OF OBJECT NOMINATION - Jo‘oraboeva Gulruh Solijonovna; Quldashev Nizomiddin Ahmadalievich; O‘rinboeva Ezozkhan Kamolovna (Western European Studies, 2024)
The article examines the naming of objects based on the principle of relativity, positivity and negativity, as well as the role of the human factor in it, on the example of toponyms of the Fergana Valley.
Keywords: onomastics; toponymy; positivity